Fixed points for Kannan type contractions in uniform spaces endowed with a graph - Aghanians, Aris; Nourouzi, Kourosh (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, we give two sufficient conditions for the existence of a fixed point for a Kannan type contraction in a p-complete separated uniform space endowed with a graph and equipped with an A- or an E-distance p. We also discuss the uniqueness of the fixed point and show that Banach and Kannan type contractions are independent.
Keywords: separated uniform space; Kannan G-p-contraction; fixed point